Photostimulation as a therapy method for spinal cord contusion while asleep and awake - Semyachkina-Glushkovskaya, Oksana V.; Sarantseva, Elena I.; Iskra, Tatiana D. (Известия Саратовского университета. Новая серия: Серия Химия. Биология. Экология)
Traumatic spinal cord injury is one of the most complex problems in modern medicine, characterized by a signifi cant number of severe consequences and complications, development of traumatic spinal cord disease with a complex of structural and functional disorders leading to limited self-care and mobility, persistent endocrine shifts and changes in internal organs and systems, loss of control of pelvic functions, high mortality rates, and an extremely high level of social and psychological maladaptation of patients. Taking into account the fact that lymphatic drainage processes in the brain are activated during sleep, attention was given to comparing the eff ects of phototherapy of injured spinal cord in mice receiving treatment while asleep or awake. Photobiomodulation therapy was used as an anti-infl ammatory and non-invasive treatment with minimal side eff ects. In the course of the study we established the presence of lymphatic structures in the animals’ spinal cord tissues. In a number of phototherapeutic eff ects during sleep we observed the following: improvement of morphological parameters of spinal cord tissues and activation of lymphatic drainage processes in the spinal cord.